Сушіння зовнішніх поверхонь нагрівання котлів ТП-10 за допомогою теплоти живильної води - Мисак, Й. С.; Кузик, М. П. (Видавництво Львівської політехніки, 2014)
Розглянуто процедуру водяного миття і подальшого сушіння котла ТП-10. Термічне сушіння зовнішніх поверхонь нагрівання котла здійснюється подачею в його пароводяний тракт живильної води з загальностанційного трубопроводу. Procedure of aquatic washing and subsequent drying of boilers TP-10 is presented. The thermal drying of external surfaces of heating of boilers is important for serving the steamaquatic highway of feedwater from the station pipeline. The optimal parameters of the drying process, especially the speed and duration of feeding feedwater were determined. Analytical dependences to describe the dynamics of change in humidity of the drying agent and the output of the gas boiler when turning on the exhauster were developed. Based on these results the time dependence of the removal of water fromthe boiler was defined. The amount of moisture remaining in the thermal drying boiler TP-10 after its washing was determined. It is approximately 3200-4000 lbs.
Keywords: миття котлів; сушіння котлів; washing of boilers; drying of boilers